A Multidimensional Analysis of Religious Extremism - Wibisono, Susilo; Louis, Winnifred R.; Jetten, Jolanda (Frontiers in Psychology, 2019)
Even though religious extremism is currently a hotly debated topic, it is often reduced to a unidimensional construct that is linked to religious violence. We argue that the contemporary use of the term ‘extreme’ fails to capture the different interpretations, beliefs, and attitudes defining extreme religious identity. To address this issue, we unpack the meaning of the term ‘extreme’ in religious contexts and answer the call by scholars to provide a more comprehensive framework that incorporates the many different dimensions that constitute religion. We develop a model of religious extremism in theological, ritual, social, and political dimensions of religion based on the variety of Islamic groups in Indonesia. Going beyond an analysis that equates Muslim extremism with violence, we argue that Muslims (or indeed any religious group) may be extreme in some dimensions but moderate in others, e.g., extreme in ritual and moderate in political. Interpreting extremism relative to these four dimensions provides new insights when examining the global issue of religious extremism and helps to better predict how religious extremism is expressed. More generally, our framework helps to develop an understanding of radicalism that goes beyond a focus on violence.